Implementation of Print Static Archive Access Services at Semarang Regency Archives and Library Office - Anugrah Theodorus Daeli; Albertoes Pramoekti Narendra; Elizabeth Sri Lestari (Lentera Pustaka: Jurnal Kajian Ilmu Perpustakaan, Informasi dan Kearsipan, 2026)
Background: Archives are important records that serve as historical “memories”. There are dynamic archives (actively used) and static archives (historically valuable, permanently stored, and need to be protected). Although static archives are open to the public, access is restricted to protect information, state interests, privacy, and due to limited facilities. This research will look at how the Semarang Regency Archives and Library Office manages and provides access to these static archives.Objective: This research aims to understand the access services for static archives at the Semarang Regency Archives and Library Agency. This includes identifying the criteria for access restrictions as well as analyzing the impact of such restrictions on the static archive collection there.Methods: This research uses qualitative methods, which means the data is in the form of descriptions of words or observations of behavior, not numbers. This method explores phenomena in their natural environment, where the researcher becomes the main data collection tool. Data is collected with various techniques (triangulation) and analyzed inductively to understand the deep meaning, not just conclude in general.Results: Access to static archives at Semarang Regency Archives and Libraries Agency is restricted by Semarang Regent Regulation No. 27/2018 to uphold information confidentiality for law enforcement and state security. The access is categorized as open or closed, with direct access to the depot or indirect access through ANRI's online portal for archive listings and digital copies. Archives are obtained from institutions through submissions and acquisitions with specific procedures, though most have been received from regional institutions irregularly. The agency aims to remind these institutions to submit archives more consistently.Conclusion: The research highlights that despite the mandate for integrated archive services by Regent Regulation No. 27/2018, Semarang Regency Archives and Library relies on a manual static archive system due to infrastructure limitations and lack of technologists. Access to archives is restricted to protect sensitive information, but efforts are in place for relevant collection evaluation and proper storage maintenance. Archives are classified based on local regulations, with efforts to align the classification system. The acquisition of archives predominantly involves local institutions but proactive strategies are needed to diversify sources. Overall, the research emphasizes the challenges faced by the Semarang Regency Archives and Library in transitioning to an integrated system, indicating the need for technological advancements and diversified acquisition sources.